Architectural inspirational through artworks - Maskuriy, Raihan; Baharuddin, Nasir; Sharif, Roslina; Ferza Nottisa,; Tor, Yen Ming; Ong, Kang Shon; Syaza Nur Asyikin, (Universiti Putra Malaysia Press, 2014)
The most challenging task for young design students is to develop ideas and convert these ideas into design products. It requires students to use cognitive skills and imaginations. However, majority of students have difficulties in ideas generation. Showing examples of previous students' works might help these students to form some ideas, but this approach will only teach students how to imitate others' works without consciously understanding the actual meaning of the idea.